PENGARUH PENGGUNAAN MEDIA MONOPOLI BAHASA TERHADAP PENGUASAAN KOSAKATA BAHASA ARAB SISWA KELAS IV MI SALAFIYAH KOTA CIREBON - Dodi Robiansyah; Ii Rahmanudin; Muhammad Arifin Hanif (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2023)
Learning media are used as a learning resource because learning media are useful for complementing, maintaining, and even improving the quality of the ongoing learning process. However, many of the students find it difficult to understand Arabic material because they do not know the meaning of the vocabulary in each Arabic sentence. so they find it difficult to understand Arabic subject matter. Therefore, this study aims to determine students' ability to learn Arabic vocabulary before using language monopoly media, to determine students' ability to learn Arabic vocabulary after using language monopoly media, and to determine the effect of using language monopoly media on the Arabic vocabulary mastery of fourth grade students MI Salafiyah Kota Cirebon. The rationale of this study is that the use of language monopoly media will make it easier for students to memorize vocabulary, so that they are able to understand learning material, especially Arabic vocabulary, because they will be trained to say vocabulary repeatedly. In this case, the vocabulary mastery of Madrasah Ibtidaiyah students will increase. Then this study used a quantitative approach with a pre-experimental design. The data collection techniques are direct observation, interviews, and tests (pretest and posttest). The data analysis techniques are the normality test, homogeneity test, and hypothesis testing. The results of this study show, first, students' ability to master Arabic vocabulary before using language monopoly media, with a minimum score of 39, a maximum score of 59, and an average of 51.50. Second, students' ability to master Arabic vocabulary after using language, monopoly media, namely a minimum score of 80, a maximum score of 100, with an average of 87.67. Third, based on the results of the independent sample test, 0.000 is obtained because the sig is smaller than 0.05, so Ho is rejected and H1 is accepted. Thus, it can be concluded that based on these data it shows that there is a significant influence from the use of language monopoly media on students' Arabic vocabulary mastery.